Clinical significance of kallikrein-related peptidase 7 (KLK7) in colorectal cancer - Talieri, Maroulio; Mathioudaki, Konstantina; Prezas, Panagiotis; Alexopoulou, Dimitra K.; Diamandis, Eleftherios P.; Xynopoulos, Dimitris; Ardavanis, Alexandros; Arnogiannaki, Niki; Scorilas, Andreas (Thrombosis and Haemostasis, 2009)
Human tissue kallikrein-related peptidases are a family of 15 secreted serine proteases, located at chromosome 19q13.4. Most of them have been reported to be potential biomarkers for several carcinomas and other diseases. Human tissue kallikrein-related peptidase 7 (KLK7) has been purified from human stratum corneum and resembles a chymotryptic endopeptidase originally called stratum corneum chymotryptic enzyme (SCCE). In this study, we examined for the first time, the prognostic value of KLK7 mRNA expression, using a semi-quantitative RT-PCR method, in 105 colorectal cancer tissues for 54 of which, paired normal colonic mucosa were available. Furthermore, we analysed the expression of KLK7 in 10 adenomas, in 18 biopsies of inflamed colon mucosa, as well as in 22 human cancer cell lines of various origin, four of them being of colon. A defined number of colon cancer samples were also examined by immunohisto-chemistry. KLK7 expression was higher in cancerous than in normal tissues. Less differentiated tumors of more advanced stage showed higher KLK7 expression. Follow-up analysis revealed that KLK7 was significantly associated with shorter overall survival (OS) and disease-free survival (DFS). In addition, selected colon cancer samples highly expressing KLK7 gene, showed intense immunohistochemical staining for KLK7, enhancing RTPCR results. Present data suggest that KLK7 gene is up-regulated in colon cancer and its expression predicts poor prognosis for colon cancer patients.
Keywords: Cell lines; colorectal cancer; human stratum corneum chymotryptic enzyme; KLK7; tumor markers